Stability of O/W Emulsion with Synthetic Perfumes Oxidized by Singlet Oxygen - Naoki Watabe; Yoshikazu Tokuoka; Norimichi Kawashima (Journal of Chemistry)
We prepared O/W emulsion composed of a synthetic perfume, n-dodecane, protoporphyrin IX disodium salt (PpIX-2Na), sodium dodecyl sulfate, and water and investigated oxidative decomposition of the synthetic perfume in the emulsion and change in the stability of the emulsion by singlet oxygen (1O2) generated by photosensitization of PpIX-2Na. We used eugenol, linalool, benzyl acetate, α-ionone, α-hexylcinnamaldehyde, and d-limonene as a synthetic perfume. The stability of the O/W emulation including eugenol and linalool significantly decreased with increasing light irradiation time. The decrease in the emulsion stability may be attributable to oxidative decomposition of eugenol and linalool by 1O2 and enlargement of the oil droplet size.